Pengaruh Daya Tarik Iklan, Kualitas Produk Dan Kepercayaan Konsumen Terhadap Minat Beli E-Commerce Tiktok Studi Kasus Jiniso - Agnes Tallo Rara; Suhardi Suhardi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the extent to which the elements of advertising appeal, product quality, and consumer trust influence the purchase intention of Jiniso products on the TikTok e-commerce platform. This study adopts a quantitative approach with a descriptive design as its main framework. The subjects of the study consisted of individuals who had made a purchase transaction for Jiniso products via TikTok in the Batam City area throughout 2025. Given that the population size cannot be identified with certainty, the sample size estimation was carried out by applying the Jacob Cohen formula and purposive sampling technique based on predetermined criteria, resulting in a total of 204 respondents. The data analysis techniques used include testing the validity and reliability of data, classical assumption tests, analysis of the influence between variables, and hypothesis testing through statistical analysis of the t-test and F-test. The findings show that the aspect of advertising appeal contributes 22.1% to the tendency to buy, while product quality contributes 40.9%, and the consumer trust factor contributes 23.6%. The results of the determination coefficient (R²) calculation show that the three independent variables together are able to explain 74.3% of the variability in consumer purchasing interest in Jiniso products, while the remaining 25.7% comes from external factors not included in this model. Statistical testing using the t-test and F-test confirms that the three factors have a significant and positive influence on increasing purchasing interest in Jiniso products through the TikTok platform in the Batam area.